ANALISIS KAMPANYE TENTANG DOXING DALAM UPAYA MENJAGA DATA PRIBADI DI MEDIA SOSIAL - Mellania, Putri (Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the #PrivacyMatters campaign conducted by Instagram in an effort to protect users' personal data and prevent doxing practices on social media. In using social media, society is required to constantly update their daily lives by sharing them using features available on these platforms. The term